Fin spine metals by LA-ICP-MS as a method for fish stock discrimination of Genidens barbus in anthropized estuaries. - Avigliano, Esteban (2020)
Fil: Avigliano, Esteban. Universidad de Buenos Aires, Facultad de Ciencias Veterinarias. Buenos Aires, Argentina.